Intellectual Capital as the Determinant of Voluntary Disclosure: A Study on Financial Sector of Bangladesh - Ahmed, Alim Al Ayub (Asian Accounting and Auditing Advancement, 2018)
The purpose of this paper is to examine empirically the impact of intellectual capital disclosure (IC) voluntarily. The empirical research is based on companies listed on the Dhaka Stock Exchange. This paper aims to investigate certain factors, which have not previously been presented in the literature, pertaining to intellectual capital performance in the Bangladeshi Banking and Insurance Sectors. An exploration of literature was performed to pick out the associated IC terminology and this examination adopts the scaffold for IC items developed by Bontis (2003). The aims of this study were to identify the determinants and the extent of intellectual capital disclosure among Bangladeshi-listed financial companies. Then disclosure of these terms is examined within the annual reports of the financial year 2011-12 of the selected listed companies. It is exposed that, only 13 terms, out of 39 terms, are disclosed and the average IC disclosure by companies in both sectors leftovers low. The banking sector has performed better than the insurance sector in terms of the number of companies reporting IC terms and an average number of IC terms disclosed by a bank is found higher than that of an insurance company. But statistical outcome shows that there is no significant difference in the mean number of companies disclosing an item of IC and the average number of IC terms disclosed by banking and insurance companies at a 5 percent level of significance.